INTENSITAS PENGGUNAAN E-LEARNING DALAM MENUNJANG PEMBELAJARAN MAHASISWA PROGRAM SARJANA (S1) DI UNIVERISTAS HASANUDDIN - Alimuddin Alimuddin; Muhammad Nadjib (KAREBA : Jurnal Ilmu Komunikasi, 2015)
Abstract This research aimed to find out (1) the learning result of students graduate program (S1) at Hasanuddin University, (2) Intensity e-learning used as media learning students graduate program (S1) at Hasanuddin University, (3) the effect intensity e-learning used as media learning for learning result students graduate program (S1) at Hasanuddin University. The Method used in the research was the quantitative descriptive, sample investigated in thee research were the students graduate Faculty of Marine Science and Fisheries and faculty of Literature Hasanuddin University. The research result showed that there is a positive influence between the intensity learning used as media learning to result learning students graduate program (S1) Hasanuddin University. The result of the simple linear regression analysis indicates the R Square value of 0.081. This indicates that the (variation of the independent variable) of the intensity e-learning used gives the contribution as much as 8.1% on the (dependent variable) of the learning result.Abstrak Penelitian ini bertujuan mengetahui (1) hasil pembelajaran mahasiswa program sarjana (S1) di Universitas Hasanuddin, (2) intensitas penggunaan e-learning sebagai media pembelajaran mahasiswa program sarjana (S1) di Universitas Hasanuddin, (3) pengaruh intensitas penggunaan e-learning sebagai media pembelajaran terhadap hasil pembelajaran mahasiswa program sarjana (S1) Universitas Hasanuddin. Metode yang digunakan adalah metode deskriptif kuantitatif, Sampel penelitian ini adalah mahasiswa program sarjana fakultas Ilmu Kelautan dan Perikanan dan fakultas Sastra Universitas Hasanuddin. Hasil penelitian menunjukkan bahwa ada pengaruh positif antara Intensitas penggunaan e-learning sebagai media pembelajaran terhadap hasil pembelajaran mahasiswa pada Program Sarjana (S1) Universitas Hasanuddin. Hasil analisis regresi linear sederhana menunjukkan nilai R Square sebesar 0,081. Hal ini menunjukkan bahwa (variasi variabel bebas) intensitas penggunaan e-learning memberikan kontribusi sebesar 8,1% terhadap (variabel terikat) hasil pembelajaran.